French wine and the Brazilian consumer - Morel de Boncourt, Antoine Marie Jean Gérard (2015)
In a more and more competitive international wine market, French exporters are looking at new markets to spread their activity. Brazil presents today a considerable potential market for wine, and it is very important for French wine exporters that are looking gain market shares to understand better its dynamics in order to shape efficient marketing strategies. The first and step is to understand the behavior of the end consumer in order to offer the right product the right way. The following dissertation has for object the analysis of the consumption habits as well as the consumer’s perception of the French wines in the Brazilian wine market. The analysis will be conducted in the light of consumer behavior; therefore special attention will be paid to Brazilian demographics, consumer habits, and market trends for wine products. More precisely, research will try to identify different groups of consumers with similar patterns, based on demographics, their consumption or potential consumption of wine, and their particular perception of French wine. The idea behind that process is to construct a frame that can help developing marketing strategies for French wines professionals in Brazil, giving potential exporters a better understanding of who they should target and how they can do it effectively. The realization of this dissertation was an important challenge, as wine consumer behavior in Brazil was not addressed entirely before. It is very difficult today for French wine exporters wishing to understand better the Brazilian wine consumer to find any study or analysis. This dissertation was thus conducted in the hope of offering them an interesting tool for constructing more efficient marketing strategies. In order to do so, literature was reviewed addressing Brazilian wine market (product specificities, production, consumer data etc). It also covered decision factors that influence consumers in their buying decisions, which is a very complex matter when it comes to wine products. Finally, literature about wine-marketing strategies was reviewed, in order to evaluate their respective potential impact as well as their relevance to the Brazilian Market. The second step of the study was the submission of questionnaires to Brazilian consumers and analyzed in order to determine their preferences and understand their perception of the French wines. The objective was to identify potential target groups for French wine producers.